Marketing Communication Strategy 5.0 Public Relations In Increasing The Number Of Students - Hilda Yulianti; Rofiq Hidayat (STKIP Singkawang, 2024)
This research aims to explore the marketing communication strategy 5.0 played by public relations in increasing student numbers. Through a qualitative approach, this research explores in depth how the practice of marketing communication strategy 5.0 is used to market the madrasah in increasing student numbers. Data was collected through a series of semi-structured interviews with various stakeholders, including madrasah management staff, teachers, parents, and the learners themselves, while the researcher also used active participation observation, as well as primary documentation. Analysis of the data provided a deeper understanding of the public relations 5.0 marketing communication strategy in increasing student numbers. The results of this study indicate that in Madrasah Ibtidaiyah Negeri 3 Jember in its marketing using 4P, namely product, which is given in the form of product innovation in the form of diverse extracurricular and madrasah activities with market needs. Price, the price offered by the madrasah is also in accordance with the surrounding community and there is transparency between the community and the madrasah. Place, the strategic location of the madrassa which is located close to people's homes makes it easier for people to reach their children to study at the madrassa, and promotion, where the madrassa promotes using social media by creating interesting content in accordance with the times and existing trends.